2021
DOI: 10.3389/fonc.2021.658234
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Application of Liquid Biopsy in Non-Hodgkin Lymphoma

Abstract: Non-Hodgkin lymphoma (NHL) is a common type of hematological malignant tumor, composed of multiple subtypes that originate from B lymphocytes, T lymphocytes, and natural killer cells. A diagnosis of NHL depends on the results of a pathology examination, which requires an invasive tissue biopsy. However, due to their invasive nature, tissue biopsies have many limitations in clinical applications, especially in terms of evaluating the therapeutic response and monitoring tumor progression. To overcome these limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 98 publications
(214 reference statements)
0
14
0
Order By: Relevance
“…DLBCL is an aggressive and heterogeneous lymphoma, and studies have shown that cfDNA may have a position in the diagnosis of the disease. Various reports have shown a higher amount of cfDNA in patients with this lymphoma compared to healthy patients, a decrease in the amount of cfDNA when the treatment is effective, and a correlation between quantification of cfDNA and adverse prognosis of the disease [16,[96][97][98][99].…”
Section: Diffuse Large B Cell Lymphomamentioning
confidence: 86%
See 1 more Smart Citation
“…DLBCL is an aggressive and heterogeneous lymphoma, and studies have shown that cfDNA may have a position in the diagnosis of the disease. Various reports have shown a higher amount of cfDNA in patients with this lymphoma compared to healthy patients, a decrease in the amount of cfDNA when the treatment is effective, and a correlation between quantification of cfDNA and adverse prognosis of the disease [16,[96][97][98][99].…”
Section: Diffuse Large B Cell Lymphomamentioning
confidence: 86%
“…Shin et al designed a panel of 66 genes associated with NHLs and analyzed the plasma cfDNA from patients with various subtypes using NGS; this study showed that the level of ctDNA was decreased in patients with response to therapy and increased in patients with disease progression [113]. However, we must be cautious because some reports have shown that some mutations, such as TP53 or DNMT3A, could have their origin in clonal hematopoiesis of indeterminate potential (CHIP) [99,114].…”
Section: Diffuse Large B Cell Lymphomamentioning
confidence: 99%
“…Tissue biopsy is an invasive examination that can only reflect the characteristics of tumors statically and locally at the biopsy location. 28 Since ctDNA is derived from tumor cells throughout the body, it circumvents common limitations of tissue biopsies by capturing the complete molecular profile of tumors, including those from inaccessible anatomic locations. 27 In recent years, ctDNA emerges as an alternative source to estimate tumor burden and detect mutational profiles, 29 as well as represents a complementary method to PET scan imaging for DLBCL diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Liquid biopsy is a noninvasive procedure that allows for the detection of evidence of tumors in the peripheral blood [ 94 ]. In recent years, much scientific effort has been invested in the development of liquid biopsy, since it may overcome some of the difficulties related with the obtention of tissue probes for pathological analysis, such as difficult anatomical access, patients in critical condition, an unjustifiable risk of surgery, limited sensitivity of imaging technics for follow-up, amongst many others [ 95 , 96 ]. There are several methods of detecting tumor traces in the blood.…”
Section: Advances In Molecular Methods and New Perspectives In Clinical Practicementioning
confidence: 99%
“…There are several methods of detecting tumor traces in the blood. Evidence of a malignancy may be present through the direct identification of circulating tumor cells, or indirectly through the investigation of genetic material released from tumor cells: DNA, microRNAs and tumor-derived exosomes [ 96 ]. DNA can be detected in the blood of virtually all individuals, and it is frequently named cell-free DNA (cfDNA).…”
Section: Advances In Molecular Methods and New Perspectives In Clinical Practicementioning
confidence: 99%